anonymous
  • anonymous
Given that h(x) = 4x+5 and (h-j)(x) = x-2, find j(x).
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
@freckles
anonymous
  • anonymous
I think I have an idea, but I don't think it is correct
anonymous
  • anonymous
Would I do 4(x-2)+5

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

mathstudent55
  • mathstudent55
h(x) = 4x+5 and (h-j)(x) = x-2, find j(x) (h-j)(x) = h(x) - j(x) x - 2 = 4x + 5 - j(x) Solve for j(x)
anonymous
  • anonymous
Ok. Would that be -7/3 ?
mathstudent55
  • mathstudent55
x - 2 = 4x + 5 - j(x) Add j(x) to both sides: j(x) + x - 2 = 4x + 5 Subtract x from both sides & add 2 to both sides: j(x) = 3x + 7
anonymous
  • anonymous
Oh ok.. And then once I plug them in together I should get x-2 right?
mathstudent55
  • mathstudent55
Let's check. We must have h(x) - j(x) = x - 2 h(x) = 4x + 5 j(x) = 3x + 7 (h-j)(x) = h(x) - j(x) = 4x + 5 - (3x + 7) = 4x + 5 - 3x - 7 = x - 2
anonymous
  • anonymous
Thank you so much! I thought it was something along the likes of that, but I just wanted to double check.
mathstudent55
  • mathstudent55
Yes, but the answer is just j(x) = x - 2 I just plugged it in to check if j(x) = x - 2 was the correct answer.
mathstudent55
  • mathstudent55
You're welcome.

Looking for something else?

Not the answer you are looking for? Search for more explanations.